Academic Placement Data and Analysis (APDA) 2021 survey of philosophy Ph.D. students and recent graduates: Demographic data, program ratings, academic job placement, and nonacademic careers. (6th December 2021) - Jennings, Carolyn Dicey; Dayer, Alex
Abstract: Doctoral graduates in philosophy are an excellent source of information about the discipline: they are at the cutting edge of research trends, have an inside view of research‐focused departments, and their employment prospects provide early insights on the future health of the discipline. This report details the results of a survey sent in 2021 to recent Ph.D. graduates and current students, as well as data‐gathering efforts by Academic Placement Data and Analysis that have taken place over the past ten years. The report especially focuses on demographic representation, program ratings, academic job placement, and nonacademic careers.